The wound healing of deep partial-thickness burn in Bama miniature pigs is accelerated by a higher dose of hUCMSCs - Lingying Liu; Xingxia Hao; Jing Zhang; Shaozeng Li; Shaofang Han; Peipei Qian; Yong Zhang; Huaqing Yu; Yuxin Kang; Yue Yin; Weiouwen Zhang; Jianmei Chen; et al. (Stem Cell Research & Therapy)
Abstract Background Deep partial-thickness burns have a significant impact on both the physical and mental health of patients. Our previous study demonstrated human Umbilical Cord Mesenchymal stem cells (hUCMSCs) could enhance the healing of severe burns in small animal burn models, such as rats. Furthermore, our team has developed a deep partial-thickness burn model in Bama miniature pigs, which can be utilized for assessing drug efficacy in preclinical trials for wound healing. Therefore, this study further determine the optimal dosage of hUCMSCs in future clinical practice by comparing the efficacy of low-to-high doses of hUCMSCs on deep partial-thickness burn wounds in Bama miniature pigs. Materials and methods The male Bama miniature pigs (N = 8, weight: 23–28 kg and length: 71–75 cm) were used to establish deep partial-thickness burn models, which used a continuous pressure of 1 kg and contact times of 35 s by the invented electronic burn instrument at 100℃ to prepare 10 round burn wounds with diameter of 5 cm according to our previous report. And then, 0 × 10^7, 1 × 10^7, 2 × 10^7, 5 × 10^7 and 1 × 10^8 doses of hUCMSCs were respectively injected into burn wounds of their corresponding groups. After treatment for 7, 14 and 21 days, the burned wound tissues were obtained for histological evaluation, including HE staining for histopathological changes, immunohistochemistry for neutrophil (MPO+) infiltration and microvessel (CD31+) quantity, as well as Masson staining for collagen deposition. The levels of inflammatory factors TNF-α, IL-1β, IL-10 and angiogenesis factors angiopoietin-2 (Ang-2), vascular endothelial growth factor (VEGF), as well as collagen type-I/type-III of the wound tissues were quantified by ELISA. Results All of doses hUCMSCs can significantly increase wound healing rate and shorten healing time of the deep partial-thickness burn pigs in a dose-dependent manner. Furthermore, all of doses hUCMSCs can significantly promote epithelialization and decreased inflammatory reaction of wound, including infiltration of inflammatory cells and levels inflammatory factors. Meanwhile, the amounts of microvessel were increased in all of doses hUCMSCs group than those in the burn group. Furthermore, the collagen structure was disordered and partially necrotized, and ratios of collagen type-I and type-III were significantly decreased in burn group (4:1 in normal skin tissue), and those of all hUCMSCs groups were significantly improved in a dose-dependent manner. In a word, 1 × 10^8 dose of hUCMSCs could regenerate the deep partial-thickness burn wounds most efficaciously compared to other dosages groups and the burn group. Conclusion This regenerative cell therapy study using hUCMSCs demonstrates the best efficacy toward a high dose, that is dose of 1 × 10^8 of hUCMSCs was used as a reference therapeutic dose for treating 20 cm2 deep partial-thickness burns wound in future clinical practice. Graphical abstract